Acute treatment of stroke: Fibrinolysis - Dalkiliç, Semih; Dalkiliç, Lütfiye Kadioğlu (Nova Science Publishers, Inc., 2024)
Stroke is an important health problem that affects more than 15 million people a year all over the world. The causes of stroke can be very different. However, the most important point in treatment is to diagnose the stroke as soon as possible and to start the appropriate treatment. The shorter the time between diagnosis and initiation of treatment, the higher the efficiency of treatment. The main purpose of stroke treatment is to reopen the vessel that is blocked by a thrombus and whose blood flow has been interrupted and to dissolve the clot. Different treatment approaches are applied. The most important of these treatment options is to dissolve the clot with anti-thrombotic drugs. Recombinant tissue plasminogen activator, known as Alteplase, is the most suitable drug, which has been approved for clinical use by the FDA and whose efficacy and safety have been proven so far. The basic principle in antithrombotic therapy is to identify patients who are suitable for this treatment. Because not every stroke patient responds to this type of drug treatment and different treatment methods are needed, such as mechanically dissolving or removing the clot. In such cases, some criteria, such as the structure of the affected vessels and the size of the region, gain importance. In this section, the hemostasis mechanism will be briefly mentioned, the physiological mechanism of dissolution of the thrombus in the vessel (Fibrinolysis) will be mentioned, and information will be given about how this mechanism is used in the treatment of stroke and different treatment methods. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Fibrinolysis; Hemostasis; Stroke; Thrombus